Flood awareness system / Ahmad Zakwan Iskandar & Muhammad Yusman Dzulkarnaen Badrul Hisham - Iskandar, Ahmad Zakwan; Badrul Hisham, Muhammad Yusman Dzulkarnaen (2015)
The flood will become too much strain to the affected persons. Nowadays, flood occurrences are more frequent not only in the rural area but also include the urban area which has a good manage drain facilities. The situation is unpredictable but one can take precaution action on risk of life and reduce the properties destruction. Just bear in mind it will happen anytime, anyplace without counter to any other else. People may need some time to prepare before the flood occurs. One system must be built to inform the affection person about the situation. So this system has been built to solve the problem that haunted them with a cheap and easy way to encounter this situation. Flood detection system is the system that being used to detect the rising water level in the river and in the tank. When the water rises, circuit will send signal to the system. The system will inform the rising of water level with sound of buzzer. The main purpose of flood detection system is to avert or minimize loss of life. This expanded vision and defined purpose of the flood detection system as a means of establishing public safety, to reduce damage to property and to relieve public anxiety.